A high-capacity high-initial-activity silicon-carbon negative electrode material, a preparation method thereof, and a battery
Patent Information
- Application Number
- CN202511199670.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-26
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2045-08-26
AI Technical Summary
但是,超微孔中硅的利用率低,放电过程中锂离子难以从超微孔中脱嵌,导致首效降低
在硅脱锂过程中,越靠内部,脱锂越困难,本发明的硅碳复合材料的多孔碳,靠内部区域的孔径较小,硅沉积量少。通过降低内部沉硅量,可有效提高硅的利用率,从而提高克容量发挥的能力,以利于提高首效;
Smart Images

Figure CN121011649B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of silicon-carbon anode materials, specifically relating to a high-specific-capacity, high-efficiency silicon-carbon anode material, its preparation method, and the battery thereof. Background Technology
[0002] The statements herein provide only background information in relation to this invention and do not necessarily constitute prior art.
[0003] To improve battery energy density, silicon anodes can effectively replace traditional graphite due to their ultra-high capacity. Vapor-deposited silicon-carbon anodes have become a research hotspot due to their excellent properties such as low expansion and good cycle life. This technology uniformly deposits silicon particles within the pores of porous carbon to form a silicon-carbon composite material. The pore size, proportion, and distribution of the porous carbon are key factors determining the material's electrical properties (such as capacity, first-cycle efficiency, and cycle life), thus becoming a focus of research.
[0004] While existing porous carbon materials exhibit pore structures with varying pore sizes, such as micropores, micropores, and macropores, each pore size plays a different role and can improve the initial efficiency and safety performance of silicon-carbon anode materials to some extent. However, the utilization rate of silicon in micropores is low, making it difficult for lithium ions to be inserted and extracted during discharge, leading to a decrease in initial efficiency. Furthermore, the specific capacity of silicon varies at different locations within the same pore; without optimization of the pore structure, the specific capacity of silicon may not be maximized. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the purpose of this invention is to provide a high-specific-capacity, high-efficiency silicon-carbon anode material, its preparation method, and a battery thereof.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solution: In a first aspect, the present invention provides a high specific capacity and high first-efficiency silicon-carbon anode material, comprising a porous carbon matrix and silicon particles deposited in the porous carbon matrix. The porous carbon matrix has a pore size gradient distribution, with the pore size increasing from the inside to the outside. The average pore size of the innermost region is 0.5-1 nm, the average pore size of the middle region is 1-5 nm, and the average pore size of the outermost region is 5-20 nm.
[0007] Secondly, the present invention provides a method for preparing the high-specific-capacity, high-efficiency silicon-carbon anode material, comprising the following steps: MOF particles were dispersed in a mesoporous silica precursor solution, and a mesoporous silica layer was coated on the MOF surface using the sol-gel method to obtain a MOF core-mesoporous shell composite template. After impregnating the MOF core-mesoporous shell composite template with a carbon source dispersion and drying it, it is first carbonized at a low temperature of 300-400℃ and then carbonized at a high temperature of 600-800℃. After carbonization, the composite template is removed, resulting in porous carbon. Silicon particles are deposited in porous carbon via chemical vapor deposition to obtain silicon-carbon composite materials.
[0008] Thirdly, the present invention provides a battery in which the active material of the negative electrode is the high-capacity, high-efficiency silicon-carbon negative electrode material.
[0009] The beneficial effects achieved by one or more embodiments of the present invention described above are as follows: In the process of silicon delithiation, the further inside the silicon, the more difficult the delithiation becomes. The porous carbon in the silicon-carbon composite material of this invention has smaller pore sizes and less silicon deposition in the inner region. By reducing the amount of silicon deposited inside, the utilization rate of silicon can be effectively improved, thereby increasing the specific capacity and thus improving the first-efficiency performance. The porous carbon in the silicon-carbon composite material of this invention has a larger pore size near the outer region, which not only helps to improve the wetting and diffusion of the electrolyte, but also allows the deposited silicon particles to have a larger particle size. Larger silicon particles have a smaller specific surface area, which can reduce the side reactions between silicon and electrolyte, thus improving the initial efficiency.
[0010] In addition, the innermost pore size of porous carbon is small, and the pore size increases from the inside to the outside, which can improve the strength and stiffness of the porous carbon skeleton and improve the structural stability of the porous carbon skeleton. Attached Figure Description
[0011] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.
[0012] Figure 1 This is a schematic diagram of the material structure prepared in the embodiments of the present invention; Figure 2 yes Figure 1 Enlarged view of point A in the middle.
[0013] Wherein, 1-porous carbon framework; 2-porous carbon internal pores; 3-silicon particles; D1 is 5-20nm, D2 is 1-5nm, and D3 is 0.5-1nm. Detailed Implementation
[0014] It should be noted that the following detailed description is illustrative and intended to provide further explanation of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0015] In a first aspect, the present invention provides a high specific capacity and high first-efficiency silicon-carbon anode material, comprising a porous carbon matrix and silicon particles deposited in the porous carbon matrix. The porous carbon matrix has a pore size gradient distribution, with the pore size increasing sequentially from the inside to the outside and interconnected. The average pore size of the innermost region is 0.5-1 nm, the average pore size of the middle region is 1-5 nm, and the average pore size of the outermost region is 5-20 nm.
[0016] The first type of pores (average pore size of 5-20nm) are larger, and the grown silicon particles are also correspondingly larger. They have a small specific surface area and are located on the outermost layer of silicon + carbon materials. Therefore, the side reactions with electrolyte during battery formation are relatively reduced, which can improve the first efficiency. At the same time, the larger the outermost pore size, the more conducive it is to the absorption and diffusion of electrolyte, improving cycle and fast charging capabilities.
[0017] Type III pores (average pore size 0.5-1 nm) have extremely small pore sizes and the lowest silicon content is deposited in them. Typically, the silicon in the innermost layer of silicon-carbon materials has a lower specific capacity than that in the outer layers. Therefore, reducing the silicon content in the innermost layer can reduce silicon waste and improve silicon utilization. Furthermore, the small pore size of the innermost layer of the pore structure makes the porous carbon more rigid and the structure more stable.
[0018] Type II pores (with an average pore size of 1-5 nm) have a suitable pore size and are the main active areas for silicon deposition, in order to obtain the best silicon particle utilization efficiency and the best electrical properties of silicon-carbon materials.
[0019] In some embodiments, the particle size of the porous carbon matrix is 3-15 μm.
[0020] In some embodiments, the porous carbon matrix has a porosity of 40-80% and a pore depth of 2.5-13 μm.
[0021] Preferably, the length of the pore region with an average pore size of 0.5-1 nm is 0.5-2.5 μm, and the length of the pore region with an average pore size of 5-20 nm is 0.5-3 μm.
[0022] Secondly, the present invention provides a method for preparing the high-specific-capacity, high-efficiency silicon-carbon anode material, comprising the following steps: MOF particles were dispersed in a mesoporous silica precursor solution, and a mesoporous silica layer was coated on the MOF surface using the sol-gel method to obtain a MOF core-mesoporous shell composite template. After impregnating the MOF core-mesoporous shell composite template with a carbon source dispersion and drying it, it is first carbonized at a low temperature of 300-400℃ and then carbonized at a high temperature of 600-800℃. After carbonization, the composite template is removed, resulting in porous carbon. Silicon particles are deposited in porous carbon via chemical vapor deposition to obtain silicon-carbon composite materials.
[0023] A two-step carbonization process helps maintain the original structure of the template. The first step, low-temperature carbonization, has minimal impact on the structure of MOF and mesoporous silica materials, avoiding the structural changes caused by direct high-temperature rapid carbonization that affect the pore structure. The second step, high-temperature carbonization, increases the degree of carbonization of the carbon material. A higher degree of carbonization results in better conductivity, but the temperature should not be too high, as excessively high temperatures can cause the carbon structure to collapse.
[0024] ZIF-8 (pore size around 0.5 nm) was used as the MOF template. Its framework channels provide ultra-micropores, while the intercrystalline gaps form micropores (1-5 nm). MOF particles were dispersed in a mesoporous silica precursor, and a layer of self-assembled mesoporous silica particles (particle size 5-20 nm) was coated on the MOF surface by a sol-gel method to form a MOF core-mesoporous shell composite template.
[0025] By constructing templates with multi-level pore structures or templates with varying pore sizes, carbon precursors form complementary multi-level carbon skeletons in the template pores. After removing the template, porous carbon materials are obtained with a continuous transition in pore size from macropores to mesopores / micropores / ultramicropores.
[0026] During high-temperature carbonization at 600-800℃, the impregnated carbon source is carbonized to form a carbon skeleton.
[0027] Silicon deposition is prepared using the most commonly used silane chemical vapor deposition method.
[0028] In some embodiments, the MOF is ZIF-8, ZIF-67, ZIF-90, or MAF-6.
[0029] In some embodiments, the mesoporous silica precursor solution mainly includes a silicon source (such as tetraethyl orthosilicate, methyl orthosilicate), a catalyst (such as ammonia), a solvent (mainly ethanol, water, etc.) and a surfactant (mainly hexadecyltrimethylammonium bromide CTAB).
[0030] In some embodiments, the thickness of the mesoporous silica self-assembled particle layer is 0.5-3 μm, and the silica particle size is 5-20 nm.
[0031] In some embodiments, the sol-gel method involves ultrasonically dispersing MOF ZIF8 particles uniformly in an ethanol solution, then slowly adding an ethanol solution containing tetraethyl orthosilicate and CTAB to the MOF dispersion, and finally slowly adding an ammonia solution to the mixed solution while stirring. The tetraethyl orthosilicate hydrolyzes on the MOF surface, forming a self-assembled mesoporous silica particle layer on the surface.
[0032] In some embodiments, the carbon source dispersion is a sucrose solution or a phenolic resin solution.
[0033] Preferably, the concentration of the sucrose solution is 1.0-1.5 g / mL; the concentration of the phenolic resin solution is 5-25 wt%, preferably a phenolic resin solution, which has a higher yield after carbonization.
[0034] In some embodiments, the drying temperature is 90-110°C.
[0035] In some embodiments, the carbonization time at 300-400℃ is 1-2 hours.
[0036] In some embodiments, the carbonization time at 600-800℃ is 1-4 hours.
[0037] In some embodiments, the mesoporous silica layer is removed by dissolving in HF solution; and the organic residues remaining after the MOF template carbonization are extracted using N,N-dimethylformamide (DMF).
[0038] Thirdly, the present invention provides a battery in which the active material of the negative electrode is the high-capacity, high-efficiency silicon-carbon negative electrode material.
[0039] The present invention will be further described below with reference to the embodiments.
[0040] Example 1 A method for preparing a high-specific-capacity, high-efficiency silicon-carbon anode material includes the following steps: (1) Preparation of porous carbon framework materials with multi-level and continuous pore size distribution ZIF-8 (pore size of about 0.4 nm) was used as the MOF template. Its framework channels provide ultra-micropores, while the intercrystalline gaps form micropores (1-5 nm). MOF particles were first dispersed in deionized water. Then, a mixed solution of mesoporous silica precursor P123 and TEOS was slowly added to the MOF dispersion. The mass ratio of TEOS to P123 was 2:1 and the concentration of P123 was 2 wt%. A self-assembled mesoporous silica layer (pore size 5-10 nm) with a thickness of 1-2 μm was coated on the MOF surface by sol-gel method to form a MOF core-mesoporous shell composite template. The composite template was impregnated with a 15wt% phenolic resin solution for 6 hours. After impregnation, it is dried and cured at 100℃ for 2 hours; After curing, it was carbonized in stages under an Ar atmosphere: low-temperature carbonization at 350℃ (preserving the MOF structure) for 2 hours; and high-temperature carbonization at 700℃ (forming a carbon skeleton) for 2 hours. After carbonization, the template is removed by dissolving the mesoporous silica layer with HF solution at a concentration of 30 wt%. After dissolution, the substrate is cleaned by rinsing with deionized water at least three times. The MOF template was then extracted with DMF solvent. After extraction, the material was centrifuged and the solid and liquid were separated. The solid was washed with deionized water more than three times and dried to obtain three types of porous carbon materials with continuously distributed pore sizes (ultramicropores 0.5-1 nm, micropores 1-5 nm, and mesopores 5-20 nm continuously distributed).
[0041] (2) Preparation of silicon-carbon material: The porous carbon material prepared in step (1) is used as a precursor. Argon gas is introduced into the fluidized bed equipment, and silane gas is introduced into the fluidized bed. The silane flow rate is 2L / min, the silane deposition temperature is 500℃, and the deposition time is 60min to obtain silicon-carbon anode material.
[0042] Example 2 (1) Preparation of porous carbon framework materials with multi-level and continuous pore size distribution: HKUST-1 (0.9 nm pore size) was used as the MOF template, and its framework channels provided ultrapores, while the intercrystalline interstices formed micropores (2-5 nm). MOF particles were first dispersed in deionized water. Then, a mixed solution of mesoporous silica precursor P123 and TEOS was slowly added to the MOF dispersion. The mass ratio of TEOS to P123 was 2:1 and the concentration of P123 was 2 wt%. A self-assembled mesoporous silica layer (pore size 5-10 nm) with a thickness of 1-2 μm was coated on the MOF surface by sol-gel method to form a MOF core-mesoporous shell composite template. The composite template was impregnated with a 15wt% phenolic resin solution for 6 hours. After impregnation, it is dried and cured at 100℃ for 2 hours; After curing, it was carbonized in stages under an Ar atmosphere: low-temperature carbonization at 350℃ (preserving the MOF structure) for 2 hours; and high-temperature carbonization at 700℃ (forming a carbon skeleton) for 2 hours. After carbonization, the template is removed by dissolving the mesoporous silica layer with HF solution at a concentration of 30 wt%. After dissolution, the substrate is cleaned by rinsing with deionized water at least three times. The MOF template was then extracted with DMF solvent. After extraction, the material was centrifuged and the solid and liquid were separated. The solid was washed with deionized water more than three times and then dried to obtain three types of continuously distributed porous carbon materials (ultramicropores 0.9-1nm, micropores 1-5nm, and mesopores 5-20nm continuously distributed).
[0043] (2) Preparation of silicon-carbon material: The porous carbon material prepared in step (1) is used as a precursor. Argon gas is introduced into the fluidized bed equipment, and silane gas is introduced into the fluidized bed. The silane flow rate is 2L / min, the silane deposition temperature is 500℃, and the deposition time is 60min to obtain silicon-carbon anode material.
[0044] Example 3 (1) Preparation of porous carbon framework materials with multi-level and continuous pore size distribution: HKUST-1 (0.9 nm pore size) was used as the MOF template, and its framework channels provided ultrapores, while the intercrystalline interstices formed micropores (2-5 nm). MOF particles were first dispersed in deionized water. Then, a mixed solution of mesoporous silica precursor P123 and TEOS was slowly added to the MOF dispersion. The mass ratio of TEOS to P123 was 2:1 and the concentration of P123 was 2 wt%. A self-assembled mesoporous silica layer (pore size 5-10 nm) with a thickness of 1-2 μm was coated on the MOF surface by sol-gel method to form a MOF core-mesoporous shell composite template. The composite template was impregnated with a 15wt% phenolic resin solution for 6 hours. After impregnation, it is dried and cured at 110℃ for 1.5 hours. After curing, it was carbonized in stages under an Ar atmosphere: low-temperature carbonization at 400℃ (preserving the MOF structure) for 1.5 hours; and high-temperature carbonization at 750℃ (forming a carbon skeleton) for 1.5 hours. After carbonization, the template is removed by dissolving the mesoporous silica layer with HF solution at a concentration of 30 wt%. After dissolution, the substrate is cleaned by rinsing with deionized water at least three times. The MOF template was then extracted with DMF solvent. After extraction, the material was centrifuged and the solid and liquid were separated. The solid was washed with deionized water more than three times and dried to obtain three types of porous carbon materials with continuously distributed pore sizes (ultramicropores 0.9-1 nm, micropores 1-5 nm, and mesopores 5-20 nm continuously distributed).
[0045] (2) Preparation of silicon-carbon material: The porous carbon material prepared in step (1) is used as a precursor. Argon gas is introduced into the fluidized bed equipment, and silane gas is introduced into the fluidized bed. The silane flow rate is 2L / min, the silane deposition temperature is 500℃, and the deposition time is 60min to obtain silicon-carbon anode material.
[0046] Comparative Example 1 The difference from Example 1 is that silicon is deposited in conventional porous carbon: conventional porous carbon has been commercialized, while Comparative Example 1 of this invention uses porous carbon material developed by Shandong Shengquan New Energy Technology Co., Ltd. The pores in this porous carbon are mainly dominated by type II pores, with micropores of 1-2 nm accounting for nearly 90%. It is mainly obtained by carbonization of phenolic resin and alkali activation to create pores. The preparation method is already known in the industry.
[0047] Conventional porous carbon materials were introduced into a fluidized bed apparatus using argon as the carrier gas, and then silane gas was introduced into the fluidized bed at a flow rate of 2 L / min. The silane deposition temperature was 500℃ and the deposition time was 60 min, resulting in a silicon-carbon composite anode.
[0048] Comparative Example 2 (1) Preparation of porous carbon framework materials with different pore sizes: The carbon precursor (sucrose precursor) is carbonized in an inert gas atmosphere to obtain carbonized material; The carbonized material was then mixed with a pore-forming agent (potassium hydroxide) at a mass ratio of 1:1.2 to obtain a mixture. The mixture was then activated in an inert atmosphere to obtain activated material. The activation method was as follows: the material was kept at 750°C for 0.6 hours, 850°C for 5 hours, and 950°C for 2 hours in sequence. The activated material was washed with water and acid in sequence and then filtered to obtain porous carbon material.
[0049] (2) Preparation of silicon-carbon materials: Same as in Example 1.
[0050] Comparative Example 3 The difference from Example 1 is that the step of coating the MOF surface with a mesoporous silica layer by the sol-gel method is omitted when preparing the porous carbon framework; otherwise, it is the same as Example 1.
[0051] Comparative Example 4 The difference from Example 1 is that the step of low-temperature carbonization at 350°C is omitted, while the rest is the same as Example 1.
[0052] Preparation of the positive electrode: Polyvinylidene fluoride (PVDF), conductive agent (SP), and positive electrode material (NCM811) were added to N-methylpyrrolidone (NMP) in a mass ratio of 1.2:1.5:97.3. The solid content of the slurry was 75%. The mixture was thoroughly stirred and homogenized. The slurry was then coated onto the surface of an aluminum current collector at a coating amount of 22 mg / cm². 2 The positive electrode sheet is obtained by drying, cold pressing, and punching.
[0053] Preparation of the negative electrode sheet: Sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber latex (SBR), conductive agent, and negative electrode active material (composed of a mixture of commercial graphite and the silicon-carbon negative electrode material prepared in Example 1 at a mass ratio of 90:10) were sequentially added to deionized water at a mass ratio of 1.7:1.8:1.5:95, with a solid content of 50%. The mixture was thoroughly stirred and mixed to obtain a slurry. The slurry was coated onto a copper foil current collector, dried, cold-pressed, and die-cut to obtain the negative electrode sheet.
[0054] The PE separator is stacked in a "Z" shape with the prepared positive and negative electrode sheets, and packaged with aluminum-plastic film to obtain the cell to be injected with electrolyte. After baking, the electrolyte (the main component of the electrolyte is LiPF6 dissolved in a mixed solvent of EC:EMC=3:7, and the concentration of LiPF6 is 1M) is injected to obtain a lithium-ion battery (button cell) with a nominal capacity of 3Ah to be tested.
[0055] Lithium-ion battery performance testing: 1. Battery internal resistance test: Use a battery internal resistance tester to test the resistance of the battery and obtain the DC internal resistance data of the battery; 2. Battery first efficiency: first lithium delithiation capacity / first lithium insertion capacity (button cell, the electrode of which is composed of the above-coated negative electrode and lithium metal sheet, and the electrolyte and separator are the same as those of the above-mentioned soft pack battery). 3. Negative electrode specific capacity test: Using button cells, the manufacturing method is the same as that used in the battery first-efficiency performance test, the specific capacity is measured by charging at 0.1C to 1.5V; 4. Battery cycle test: 25℃ 1C / 1C cycle test, conducted using the Blue Electric test system.
[0056] Table 1 Battery internal resistance, initial battery efficiency, battery capacity, and cycle data
[0057] Test Result Analysis In Table 1, the internal resistance of the batteries is generally similar. The internal resistance of silicon-carbon materials prepared from porous carbon with different pore sizes is likely mainly related to the relative amount of silicon. The total deposited silicon content is controlled similarly in the embodiments and comparative examples of this invention, hence the small difference in internal resistance. However, in terms of specific capacity, Example 1 has less deposited silicon due to the smaller pore size of the innermost layer, and the innermost silicon is more difficult to delithiate, thus limiting the specific capacity and making it difficult to achieve its full potential. Example 1 has the highest usable silicon content, resulting in the best specific capacity and initial efficiency. This is also due to the relatively larger size of the outermost silicon particles, which reduces side reactions with the electrolyte, leading to a higher initial efficiency.
[0058] In Example 2, the increased pore size of the innermost layer led to a higher silicon content deposited in the inner layer, but the lower silicon utilization rate in the innermost layer. Therefore, the specific capacity and initial efficiency were slightly lower than in Example 1. In Example 3, by appropriately increasing the carbonization temperature during carbonization, the carbonization time could be reduced accordingly, achieving the same technical effect.
[0059] Comparative Example 1 is a silicon-carbon material prepared using conventional porous carbon. The pore size of conventional porous carbon is mainly close to that of Class II pores, and the resulting silicon particle size is generally smaller than that of Class I pores. This leads to more side reactions with the electrolyte, resulting in lower initial efficiency and specific capacity of Comparative Example 1.
[0060] Comparative Example 2 uses publicly available technology. The pore structure of the three pore sizes is not designed to be continuously distributed from the outside in, and the smallest pore size is not explicitly placed in the innermost layer. This results in a higher silicon deposition amount in the micropores compared to Examples 1 and 2. Furthermore, the largest pore size is not positioned in the outer layer to reduce side reactions between silicon and the electrolyte. Therefore, the overall first-efficiency and specific capacity are lower than in Examples 1 and 2. Thus, although both examples have multi-level pore sizes, the location of the pores not only affects the silicon specific capacity but also the side reactions at the silicon-electrolyte interface.
[0061] Comparative Example 3 omits the step of preparing a self-assembled mesoporous silica particle layer using sol-gel. The resulting porous carbon structure only has three types of pores and two types of pores, lacking the outermost large-sized type one pores, which is not conducive to electrolyte wetting. At the same time, the larger specific surface area of the type two pores will lead to an increase in side reactions with the electrolyte. Therefore, the initial efficiency is significantly lower than that of Example 1.
[0062] Comparative Example 4 uses direct high-temperature carbonization, omitting the low-temperature carbonization process. This carbonization method is not conducive to maintaining the ordered pore structure, thus affecting silicon deposition and resulting in significantly lower first-efficiency and cycle performance in Comparative Example 4.
[0063] A well-designed and regionally distributed pore structure is beneficial for improving the overall specific capacity and first-efficiency of silicon-carbon. Cycling data shows that, overall, the cycling performance of vapor-deposited silicon-carbon is excellent with little difference. However, the hierarchical pore structure continuously distributed from the outside to the inside in this invention, with the inner layer designed with the smallest pore size, improves the structural stability of porous carbon, thus exhibiting a slight advantage.
[0064] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a high-specific-capacity, high-efficiency silicon-carbon anode material, characterized in that: Includes the following steps: MOF particles were dispersed in a mesoporous silica precursor solution, and a mesoporous silica layer was coated on the MOF surface using a sol-gel method to obtain a MOF core-mesoporous shell composite template; the MOF was ZIF-8, ZIF-67, ZIF-90 or MAF-6; the thickness of the mesoporous silica layer was 0.5-3 μm, and the particle size of the silica particles in the mesoporous silica layer was 5-20 nm; After impregnating the MOF core-mesoporous shell composite template with a carbon source dispersion and drying it, it is first carbonized at a low temperature of 300-400℃ for 1-2 hours, and then carbonized at a high temperature of 600-800℃ for 1-4 hours. After carbonization, the composite template is removed, resulting in porous carbon. Silicon particles are deposited in porous carbon via chemical vapor deposition to obtain silicon-carbon composite materials. Silicon-carbon composites include a porous carbon matrix and silicon particles deposited within the porous carbon matrix; The porous carbon matrix has a pore size gradient distribution, with the pore size increasing sequentially from the inside to the outside and interconnected. The average pore size of the innermost region is 0.5-1 nm, the average pore size of the middle region is 1-5 nm, and the average pore size of the outermost region is 5-20 nm.
2. The method for preparing high-specific-capacity, high-efficiency silicon-carbon anode material according to claim 1, characterized in that: The carbon source dispersion is a sucrose solution or a phenolic resin solution; the concentration of the sucrose solution is 1-1.5 g / ml; the concentration of the phenolic resin solution is 5-25 wt%.
3. The method for preparing the high-specific-capacity, high-efficiency silicon-carbon anode material according to claim 1, characterized in that: The mesoporous silica layer was removed by dissolving in HF solution; the residual organic matter after carbonization of the MOF core-mesoporous shell composite template was extracted by N,N-dimethylformamide (DMF).
4. A high-specific-capacity, high-efficiency silicon-carbon anode material, characterized in that: It is prepared by the preparation method of the high specific capacity and high first-efficiency silicon-carbon anode material according to any one of claims 1-3.
5. The high-capacity, high-efficiency silicon-carbon anode material according to claim 4, characterized in that: The porous carbon matrix has a particle size of 3-15 μm; the porosity of the porous carbon matrix is 40-80%, and the pore depth is 2.5-13 μm.
6. The high-specific-capacity, high-efficiency silicon-carbon anode material according to claim 4, characterized in that: The length of the pore region with an average pore size of 0.5-1 nm is 0.5-2.5 μm, and the length of the pore region with an average pore size of 5-20 nm is 0.5-3 μm.
7. A battery, characterized in that: The active material of its negative electrode is the high specific capacity and high first-efficiency silicon-carbon negative electrode material as described in any one of claims 4-6.
Citation Information
Patent Citations
Silicon-carbon composite material, preparation method thereof, negative electrode material and lithium ion battery
CN117352685A
Silicon-carbon negative electrode material, negative electrode and lithium ion battery
CN118412459A